Fabrication of anthracite-derived multicolor graphene quantum dots for their potential application in nanomedicine - Hongyu Pan; Jiahe Chen; Weifeng Zhang; Liuhao Chen; Ji Young Yoon; Bin Li; Kai Yu (Exploration of BioMat-X)
Aim: This study aims to discover an alternative precursor with abundant source and low cost for multicolor graphene quantum dots (GQDs) preparation and application. Methods: In the current study, anthracite-derived multicolor GQDs were prepared at different reaction temperatures (100°–150°C), referring to the GQDs 100, GQDs 120, GQDs 130, and GQDs 150. Results: The GQDs 100, GQDs 120, GQDs 130, and GQDs 150 solutions were found to be orange-red, yellow-green, green, and blue under 365 nm excitation UV (ultraviolet) lamp, respectively. The X-ray photoelectron spectroscopy (XPS) data suggests high temperature intensifies oxidation of the amorphous sp3 carbon, resulting in GQDs with higher crystalline structure (Csp2). Compared with the GQDs 100 and GQDs 120, the GQDs 130 and GQDs 150 showed much better biocompatibility, which may attribute to their higher Csp2 composition and smaller size. Conclusions: The results suggest that GQDs 130 and GQDs 150 are ideal candidates for nanomedicine applications, e.g., drug/gene delivery and bio-imaging, etc.